Cone-Beam Computed Tomography for managing impacted canine in orthodontics. - Md Nazmul Hasan; Shirin Sultana Chowdhury; SM Abdul Quader (Update Dental College, 2014)
Radiographic interpretation and diagnosis of dental impactions have always posed a great challenge to the orthodontist to manage such case. This could largely be attributed to the limitations posed by the conventional two-dimensional (2D) imaging modalities. Dental impactions, which can position into various underlying locations, can be evaluated accurately using cone beam computed tomography (CBCT) three-dimensional (3D) imaging, rather than conventional 2D radio-imaging. This article report a case of orthodontic management of impacted canine of a 13 years old boy where conventional 2D radio-imaging diagnosis are modified by cone beam computed tomography (CBCT). DOI: http://dx.doi.org/10.3329/updcj.v3i2.18002 Update Dent. Coll. j: 2013; 3 (2): 61-64